Relationship between eWOM and purchase intention: Moderating role of culture (Evidence from University students of Pakistan) - Shaikh Obaidullah; Asad Shahbaz; Tariq Majeed (Business Review, 2022)
This study is an attempt to find out the relationship between eWOM and Purchase Intention (PI) with the moderating role of culture among the varsities students in Khyber Pakhtunkhwa. For this purpose data was collected from business and management students of various public and private sector universities. The adopted version of constructs was used to obtain the data. The result indicates that the Consumer Review (CR), Brand Image (BI) and Source Credibility (SC) attributes of eWOM have a significant relationship with (PI), while Brand Equity (BE) shows an insignificant relationship with PI. Interestingly findings from a cultural perspective indicate no interactional effect. On the basis of results, it can be stated that (BE) is not part and parcel of eWOM but still it is an important characteristic of the online shopping process. Findings recommend that the current model may be used in other universities of various provinces across Pakistan.